WITHDRAWN: Myoinositol supplementation for the prevention of gestational diabetes in at-risk patients. Systematic review and meta-analysis - Anthéa Bertrand; Denis Gallot; Bruno Pereira; Amélie Delabaere; Amélie Delabaere; Anthéa Bertrand; Denis Gallot; Igor Tauveron; Marion Rouzaire; Bruno Pereira (Elsevier, 2023)
This article has been withdrawn: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy).This article has been withdrawn at the request of Author.The publisher apologizes to the readers for this unfortunate error.